PEMBUATAN MESIN PENGIRIS BAWANG - Ricky Aldian Desrizal; Rivanol Chadry; Hendri Candra Mayana (Politeknik Negeri Padang, 2019)
The main goal to be achieved is to be able to make an onion slicing machine so that it can answer the problem if the onion slicing is carried out in a larger capacity. The onion slicing machine is made to support the increase in the production of shallot slices, which are ready to be fried for the production of scallion onions in household industries. In a small scale, the work can be done manually with a knife or other simple cutting tool. Problems will arise if large quantities of sliced or cut production are available. In order to facilitate the community in processing shallots and learn about the problems, namely how to produce a shallot slicing machine with uniform slices results using different slope angles on the knife. the working principle of this machine is the Onion which has been peeled dry skin inserted into the funnel then the plate on the back of which has a knife, will rotate because it is driven by an electric motor. As a result of the rotation the onion will be sliced and the slice will fall down, and below it a container will be used as a cross section of the onion which has been finished sliced as a result